2004
DOI: 10.2174/0929867043456287
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Molecular Interactions in silico: I. A Guide to Pharmacophore Identification and its Applications to Drug Design

Abstract: A major goal in contemporary drug design is to develop new ligands with high affinity of binding toward a given protein receptor. Pharmacophore, which is the three-dimensional arrangement of essential features that enable a molecule to exert a particular biological effect, is a very useful model for achieving this goal. If the three-dimensional structure of the receptor is known, pharmacophore is a complementary tool to standard techniques, such as docking. However, frequently the structure of the receptor pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
96
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(99 citation statements)
references
References 90 publications
0
96
0
3
Order By: Relevance
“…The presence of -GLY-residue in the triple helix is of importance in the stability of the triple helix motif in collagen structure. CGD is designed with the amino acid residue sequence of (PRO-HYP-GLY) 4 -(PRO-HYP-ALA)-(PRO-HYP-GLY) 5 and was selected because it has been synthesized and crystallographically characterized by Bella et al [12] as an important triple helix motif with a surrounding hydration structure. This structure was extracted from RCSB PDB [13] file 1CGD.…”
Section: Direct (Target-based) Docking Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The presence of -GLY-residue in the triple helix is of importance in the stability of the triple helix motif in collagen structure. CGD is designed with the amino acid residue sequence of (PRO-HYP-GLY) 4 -(PRO-HYP-ALA)-(PRO-HYP-GLY) 5 and was selected because it has been synthesized and crystallographically characterized by Bella et al [12] as an important triple helix motif with a surrounding hydration structure. This structure was extracted from RCSB PDB [13] file 1CGD.…”
Section: Direct (Target-based) Docking Methodsmentioning
confidence: 99%
“…Bella et al showed that ALA substitution for GLY in the (PRO-HYP-GLY) sequence causes a slight expansion of the triple helix locally at the site of substitution. The residue sequence in QSU is given by (PRO-HYP-GLY) 4 -(GLU-LYS-GLY)-(PRO-HYP-GLY) 5 . The QSU model was synthesized and crystallographically characterized by Kramer et al [14] and is designated as 1QSU in the RCSB PDB.…”
Section: Direct (Target-based) Docking Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given a set of active molecules, pharmacophore methods involve analysing the molecules to identify pharmacophoric features (atoms or functional groups that can potentially interact with atoms in the binding site) and then aligning the active conformations of the molecules such that their corresponding pharmacophoric features are overlaid. A recent review on alignment methods is provided by Lemmen and Lengauer [1] and reviews on pharmacophore methods can be found in references [2][3][4].…”
Section: Introductionmentioning
confidence: 99%